A dictionary of legal English collocations as an aid for mastering the legal English genre - Mroczyńska, Katarzyna (LingBaW. Linguistics Beyond and Within, 2020)
The article begins with a brief overview of collocations and their features as being central to legal language and, as such, worth studying, especially in view of the fact that legal language studies tend to be mostly interested in terminology rather than phraseology. To bridge this gap, the article offers a tool for legal English learners, i.e. the dictionary of legal English collocations based on judgments of the UK Supreme Court. Our dictionary project is aimed at analysing the corpus we created, using Sketch Engine software, a cutting-edge lexicographic tool which enables the uploading and exploration of users’ own corpora. The project will focus on analysing bipartite legal English collocations appearing in the corpus. The next stage of the project will be the preparation of the final product of our research, i.e. a dictionary of legal English collocations. We believe that such a dictionary will prove a useful aid for mastering the conceptual structure of legal English.